Resolva as expressões abaixo:
A)
![( - 3)^{2} + ( - 3 + 7)^{2} + \sqrt{9} = ( - 3)^{2} + ( - 3 + 7)^{2} + \sqrt{9} =](https://tex.z-dn.net/?f=%28+-+3%29%5E%7B2%7D++%2B+%28+-+3+%2B+7%29%5E%7B2%7D++%2B+%5Csqrt%7B9%7D+%3D+)
B)
![( - 35) + ( - 90) + ( - 3)^{2} = ( - 35) + ( - 90) + ( - 3)^{2} =](https://tex.z-dn.net/?f=%28+-+35%29+%2B+%28+-+90%29+%2B+%28+-+3%29%5E%7B2%7D++%3D+)
C)
![( -5 \: . \: 4^{2} ) + ( - 7 + 4)^{2} - 3^{2} = ( -5 \: . \: 4^{2} ) + ( - 7 + 4)^{2} - 3^{2} =](https://tex.z-dn.net/?f=%28+-5+%5C%3A+.+%5C%3A+4%5E%7B2%7D+%29+%2B+%28+-+7+%2B+4%29%5E%7B2%7D++-+3%5E%7B2%7D+%3D+)
D)
![( - \sqrt{4})^{2} - \sqrt{9 + 16} = ( - \sqrt{4})^{2} - \sqrt{9 + 16} =](https://tex.z-dn.net/?f=%28+-++%5Csqrt%7B4%7D%29%5E%7B2%7D++-++%5Csqrt%7B9+%2B+16%7D++%3D+)
E)
![( - \sqrt{16 + 20} ) + ( - 7)^{2} = ( - \sqrt{16 + 20} ) + ( - 7)^{2} =](https://tex.z-dn.net/?f=%28+-++%5Csqrt%7B16+%2B+20%7D+%29+%2B+%28+-+7%29%5E%7B2%7D+%3D+)
F)
![( -3 - 7 - 1 - 10)^{2} + ( - 2)^{3} ( -3 - 7 - 1 - 10)^{2} + ( - 2)^{3}](https://tex.z-dn.net/?f=%28+-3+-+7+-+1+-+10%29%5E%7B2%7D+%2B+%28+-+2%29%5E%7B3%7D+)
Soluções para a tarefa
Respondido por
1
A) ( 9 ) + ( 4 ){2} + 3
9+16+3
"28"
B) -35-90+9
"134"
C)-80 + (-3){2} - (-3){2}
-80 + 9 - 9
"-80"
Perguntas interessantes
História,
10 meses atrás
Português,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Psicologia,
1 ano atrás